Genetic Diversity and Affinity Among Five Tibeto-Burman Tribal Populations of Northern India: A Study on Eight Alu Markers. Issue 1 (June 2019) - Venugopal, Pulamaghatta N.; Rawat, Bimal; Shantanu, Kumar; Mukherjee, Koel; Alam, Abrar; Pawar, Shafali; Harashawaradhana
Abstract: The study attempts to ascertain an analysis of eight Arthrobacter luteus (Alu) insertion loci (ACE, TPA25, PV92, HS4.32, FXIIIB, D1, A25, B65) carried out in five tribal populations (Raji, Buxa, Jaunsari, Tharu and Bhotia) of Uttarakhand, Northern India. Total genomic DNA was extracted and amplification of genomic DNA by PCR analysis was carried out to examine the distribution of Alu (+) and Alu (–) genotypes from eight Alu loci. Genetic distance, genetic identity, pairwise Fst values and corresponding p values were computed between each pair of populations through analysis of molecular variance (AMOVA) for each Alu loci. The populations exhibited high levels of intra population variations and low levels of inter population differentiation with the average Fst value of inter population being 0.05896, which was expected to be more as the Fst value of intra population was 0.06780. Phylogenetic tree was constructed by using the neighbour-joining (NJ) method and multidimensional (MDS) plot to trace out the genetic affinity between populations. The present data showed that Raji and Buxa community were an ancestral population and Jaunsari, Tharu and Bhotia were diverged latter from Buxa community. The present study is an effort to generate a basic gene frequency distribution data at eight polymorphic Alu loci among five autochthonous groups of Uttarakhand.